Praktikum Di Rumah (PDR) Morfologi Tumbuhan Melalui Pemanfaatan Lingkungan - Tri Wahyu Agustina; Asrianty Mas'ud (Al-Alam: Islamic Science Education Journal, 2022)
AbstractThe research aims to describe the PDR Plant Morphology learning process, conduct a performance assessment of student image products, and the obstacles faced by students. Qualitative descriptive research method using a sample of one class selected purposively totaling 39 students. The practicum uses a combination of E-Knows Learning Management System (LMS) facilities and other online systems. The research instruments were in the form of rubrics and performance scoring on image products, questionnaires, interview formats, video records of observation activities, and practicum notes. Descriptive data analysis and percentages made on certain criteria. The PDR process includes eight practicum titles through observation of plant parts guided by PDR performance assignments and research instruments. The results of the performance assessment of the image product show a tendency to increase the criteria very well. The student's constraints are mainly regarding the availability of plant materials in the environment and the suitability of the images with plant materials. Students are able to independently do PDR, try to find plant materials around their environment, look for alternative materials, and look for information about plant materials.